Do firms put their money where their mouth is? Sociopolitical claims and corporate political activity - Preuss, Susanne; Max, Malte M. (Accounting, Organizations and Society, 2024)
Firms increasingly respond to stakeholder demands by making public claims about their stances on polarizing issues, but at the same time their political activities may contradict their claims. We analyze the extent to which firms' sociopolitical claims and their political action committee contributions align. We develop a dictionary of claims related to diversity and environmental protection based on word combinations in firm communications and link firms' political contributions to candidate approval ratings provided by third-party advocacy groups. While firms generally donate mostly to lower-rated politicians (i.e., those with lower environmental and human rights ratings), firms making more sociopolitical claims donate relatively more to higher-rated politicians. The latter is consistent with political alignment but also has further limit: While firms with more claims donate more to higher-rated politicians, they donate no less to lower-rated politicians. Moreover, government subsidies, politicians’ power, and community pressure for diversity and environmental disclosures reduce political alignment.